CCR2 on peripheral blood CD14(+)CD16(+) monocytes correlates with neuronal damage, HIV-associated neurocognitive disorders, and peripheral HIV DNA: reseeding of CNS reservoirs? - Veenstra, Mike (J Neuroimmune Pharmacol, 2018)
HIV-associated neurocognitive disorders (HAND) occur in ~50% of HIV infected individuals despite combined antiretroviral therapy. Transmigration into the CNS of CD14(+)CD16(+) monocytes, particularly those that are HIV infected and express increased surface chemokine receptor CCR2, contributes to neuroinflammation and HAND. To examine whether in HIV infected individuals CCR2 on CD14(+)CD16(+) monocytes serves as a potential peripheral blood biomarker of HAND, we examined a cohort of 45 HIV infected people. We correlated CCR2 on CD14(+)CD16(+) monocytes with cognitive status, proton magnetic resonance spectroscopy ((1)H-MRS) measured neurometabolite levels, and peripheral blood mononuclear cell (PBMC) HIV DNA copies. We determined that CCR2 was increased specifically on CD14(+)CD16(+) monocytes from people with HAND (median [interquartile range (IQR)]) (63.3 [51.6, 79.0]), compared to those who were not cognitively impaired (38.8 [26.7, 56.4]) or those with neuropsychological impairment due to causes other than HIV (39.8 [30.2, 46.5]). CCR2 was associated with neuronal damage, based on the inverse correlation of CCR2 on CD14(+)CD16(+) monocytes with total N-Acetyl Aspartate (tNAA)/total Creatine (tCr) (r(2) = 0.348, p = 0.01) and Glutamine-Glutamate (Glx)/tCr (r(2) = 0.356, p = 0.01) in the right and left caudate nucleus, respectively. CCR2 on CD14(+)CD16(+) monocytes also correlated with PBMC HIV DNA copies (ρ = 0.618, p = 0.02) that has previously been associated with HAND. These findings suggest that CCR2 on CD14(+)CD16(+) monocytes may be a peripheral blood biomarker of HAND, indicative of increased HIV infected CD14(+)CD16(+) monocyte entry into the CNS that possibly increases the macrophage viral reservoir and contributes to HAND.